Developing Prophetical Stories as A Characterbased English Learning Source - Ain, Nurul (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2014)
The purpose of this study is to develop the stories as the learning sources for teaching character at English lesson. This research was conducted by using research and developmental design (R & D) because the goal is to develop a product, i.e. the translated stories of Prophets. By developing the adapted model of Borg and Gall (1983), some procedures had been carried out. The product of the research is a book consisting of the translated stories of Prophet which were reviewed by experts in terms of its plot, content, language and design. In short, through this story book of Prophets, students and readers can learn the virtuous - worthy character - of Prophets as the good model for them. Besides, they can also learn English Language, especially in increasing their vocabulary in English. The suggestion given to the product of research was related to quantity of Prophet stories. Since this book just contains the story of the outstanding Prophets, it was suggested to cover all the Prophet stories for the next study.